A norma dos "bons costumes" e as resistências femininas nas obras de João Gumes (Alto Sertão Baiano, 1897-1930) - Nogueira, Maria Lúcia Porto Silva (2010)
This research has as its object of analysis the gender representations in the Alto Sertão of Bahia, at the turn of the XIX century and the first decades of the XX century. It aims to evidence some cultural practices and social tensions that permeated the experiences of women and men in the society at that time. Based on João Gumes‟s literature, the intellectual backcountry man who described that region in his novelistic plots, it was possible to glimpse the details from the public-private in a dynamic full by the dominant moral values of that period and linked with a strong tradition. Gumes announced the backcountry reality, denounced social injustices and defended the residents from that region, but it wasn‟t his objective to release efforts in order to extinguish socio-cultural stereotypes from gender relationships or to criticize prejudices that existing about the feminine world. In the dialogue with these searches, the analysis focused on differentiated documents, emerging other visions from that same time. In a dialectic and dialogical posture this research aimed to focalized the experiences and women‟s daily actions, finding female identities in different rhythms permanencies, changes, resistances, transgressions despite the set of standards and beliefs that were imposed, at that time, in the context from the backcountry culture